Extracorporeal lithotripsy of pancreatic stones in patients with chronic pancreatitis and pain: a prospective follow up study. Issue 7 (July 1992) - Sauerbruch, T; Holl, J; Sackmann, M; Paumgartner, G
Abstract : Extracorporeal shock wave lithotripsy of pancreatic duct stones (largest stone 12 (SD) 6 mm) was performed in 24 patients with abdominal pain and a dilated duct system (main pancreatic duct 10 (3) mm). The procedure was well tolerated in all but two patients, who had a mild pancreatitic attack immediately after lithotripsy. Disintegration of the stones was achieved in 21 patients. This allowed complete clearance of the duct system by an endoscopic approach in 10 (42%) patients and partial clearance in 7 (29%) patients. Within a mean follow up period of 24 (14) months half of the patients showed complete or considerable relief of pain and alleviation of symptoms was achieved in seven patients. Relief of pain occurred more often after complete ductal clearance. There were no fatalities within the follow up period. These findings underline the value of a combined non-surgical approach, using endoscopy and adjuvant shock wave lithotripsy to patients with large pancreatic calculi and pain attacks.